High Productivity Makes Mangroves Potentially Important Players in the Tropical Silicon Cycle - Elizondo, Elani B.; Carey, Joanna C.; Al-Haj, Alia N.; Lugo, Ariel E.; Fulweiler, Robinson W. (Frontiers in Marine Science, 2021)
Over the last two decades, recognition of the important role terrestrial plants play in regulating silicon (Si) cycling has emerged. Si improves plant fitness by protecting them from abiotic (e.g., desiccation) and biotic (e.g., fungal attack) stressors. Once incorporated into plant biomass this biogenic Si is more bio-available than the lithogenic material from which it was ultimately derived. Thus plants play a key function in regulating the amount and timing of Si availability in downstream ecosystems. Recent work has highlighted the importance of salt marshes in the temperate Si cycle. However, the role of their tropical counterparts, mangroves, has largely gone unexplored. Here we report foliar concentrations of plant Si (as %Si by dry weight) for four Caribbean mangrove species: Conocarpus erectus (buttonwood), Laguncularia racemosa (white mangrove), Avicennia germinans (black mangrove), and Rhizophora mangle (red mangrove). Overall, the median Si concentration was low (0.07%) and did not vary among plant part (e.g., foliage, twig, and propagule). There was also little variation in Si among species. Using literature values of aboveground net primary production, and the concentrations reported here, we estimate an aboveground mangrove Si uptake rate of 2–10 kg Si ha–1 year–1. These rates are on par with rates reported for temperate and boreal forests as well as low nutrient salt marshes, but lower than estimates for high nutrient salt marshes. Thus, despite the low Si concentrations observed in mangroves, their high productivity appears to make them a hot spot of Si cycling in tropical coastal systems.